A miniaturized spray‐assisted fine‐droplet‐formation‐based liquid‐phase microextraction method for the simultaneous determination of fenpiclonil, nitrofen and fenoxaprop‐ethyl as pesticides in soil samples. (16th October 2020) - Turan, Nouha Bakaraki; Bakirdere, Sezgin
Abstract : Rationale: Pesticides are a group of micropollutants that persist for a long time in the environment and pose threats to life. Much effort has been devoted to developing pre‐concentration methods capable of producing samples suitable for the detection of pesticides. However, better methods are still required to detect these compounds when they are present in trace concentrations in soils. Method: Spray‐assisted fine‐droplet‐formation‐based liquid‐phase microextraction was used to prepare soil samples containing three different pesticides, fenpiclonil, nitrofen and fenoxaprop‐ethyl, for subsequent analysis by gas chromatography/mass spectrometry (GC/MS). A spraying apparatus was used for the dispersion of the extraction solvent into the sample/standard solution to improve the extraction efficiency. Optimization studies were performed to lower the detection limits of these analytes and the results obtained by the application of the newly developed system were compared with those obtained using the conventional GC/MS method. Results: A calibration curve over the range 5.0–100 μg L −1 was obtained under the optimal conditions. The limits of detection and quantification were 1.56–1.80 μg L −1 and 5.21–5.98 μg L −1, respectively. The enhancements in detection ability over the conventional method for the three tested pesticides were 188.01, 176.96 and 517.14 for fenpiclonil, nitrofen and fenoxaprop‐ethyl, respectively Recovery studies performed in soil samples were satisfactory reflecting accurate applicability of the developed method. Conclusions: The developed microextraction method is a time‐saving and simple version of the traditional dispersive liquid–liquid microextraction method that also reduces the use of dispersive solvents.